2023
DOI: 10.3390/su15021340
|View full text |Cite
|
Sign up to set email alerts
|

How Tourist Experience Quality, Perceived Price Reasonableness and Regenerative Tourism Involvement Influence Tourist Satisfaction: A Study of Ha’il Region, Saudi Arabia

Abstract: This study attempts to examine the interactions between the tourist experience quality, perceived price reasonableness, and regenerative tourism involvement variables and tourist satisfaction by taking into account the moderating effects of tourist destination loyalty and destination image. The survey was circulated among international tourists visiting the Ha’il region of Saudi Arabia. This study used structural equation modeling (SEM) to analyze the data collected. The results showed significant and positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 100 publications
2
17
0
Order By: Relevance
“…Thus, a high-quality experience in green tourism has the potential to influence the satisfaction of environmentally conscious customers and motivate tourists to play a more active role in preserving nature. This aligns with research conducted by , Rehman et al (2023), andHossain et al (2023), which indicates that the quality of experience significantly and positively influences tourists' satisfaction with environmentally friendly tourist destinations (Customer Green Satisfaction).…”
Section: Introductionsupporting
confidence: 88%
“…Thus, a high-quality experience in green tourism has the potential to influence the satisfaction of environmentally conscious customers and motivate tourists to play a more active role in preserving nature. This aligns with research conducted by , Rehman et al (2023), andHossain et al (2023), which indicates that the quality of experience significantly and positively influences tourists' satisfaction with environmentally friendly tourist destinations (Customer Green Satisfaction).…”
Section: Introductionsupporting
confidence: 88%
“…The study found that tourists' perception of existential authenticity impacted satisfaction, while objective and constructive authenticity did not directly influence satisfaction [13]. Rehman et al (2023) surveyed international tourists in Khel, Saudi Arabia, and the results showed that enjoyment, destination loyalty, and destination image significantly and positively impacted tourists' satisfaction [14]. Jebbouri et al (2022) focused on tourist destinations with cultural heritage and discussed the relationship among destination image building, tourist satisfaction, and tourist trust.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Shaykh-Baygloo (2021) used a scale to study the TX of international travelers to a destination [105]. Rehman et al (2023) studied the impact of TX on the perceived price reasonableness, regenerative tourism involvement, and the moderating effects of tourist destination loyalty and destination image [151]. Bezerra and Gomes (2019) studied passengers' loyalty to an airport in the multi-airport area [152].…”
Section: Rq2: What Are the Tx Dimensions And What Factors Influence Tx?mentioning
confidence: 99%